RESPONDing to Migration: A Holistic Perspective on Migration Governance - Cetrez, Andreas Onver; Barthoma, Soner (Studies in Global Migration: Societal Challenges, 2022)
"What's past", as the famous line in Shakespeare's The Tempest has it, "is prologue". Just as this edited volume is being compiled in 2021--some six years after the 2015 refugee emergency--developments in Afghanistan and the Polish-Belarus border appear once again to be leading to a new migration emergency. This volume takes up the challenge of providing a comparative understand-ing of migration regimes and practices and their consequences for political systems and the people who have fled their homelands due to conflict, war and poverty between 2011 and 2020. Empirically, the chapters included in this volume are based on an impressive amount of empirical material gathered in 11 countries (Iraq, Lebanon, Turkey, Greece, Italy, Hungary, Austria, Poland, Germany, the UK and Sweden) within the framework of the Horizon 2020 project, RESPOND. RESPOND - Multilevel Governance of Mass Migration in Europe and Beyond (2017-2021) was funded by the European Commission to study migration holistically at the macro, meso and micro levels in order to understand the connections between policies, practices and experiences. The chapters in this volume provide a unique contribution to our understanding of the trends of re nationalization and externalization in migration and asylum policies in the aftermath of the "migration crisis" of 2015, as well as the reasons behind the failure of migration governance at both national and international levels. Just as importantly, the volume offers an anthropological gaze on overlooked aspects of refugee agency, well-being, psycho-social health and belonging in post-migration processes